2004
DOI: 10.1007/s00192-004-1150-z
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated glycosaminoglycans of the vagina and perineal skin in pre- and postmenopausal women, according to genital prolapse stage

Abstract: The aim of this study was to analyze the amount and types of sulfated glycosaminoglycans (GAGs) of the extracellular matrix (ECM) in the posterior vaginal wall and perineal skin in menacme and postmenopausal women, according to genital prolapse stage. Samples of vaginal tissue and perineal skin were obtained from 40 women who underwent vaginal surgery. Sulfated glycosaminoglycans were extracted by extensive tissue maxatase digestion, submitted to electrophoresis on agarose gel, and their concentrations were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In a study comparing HS expression in skin and mucosa, more GAGs were found in vaginal tissue than in perianal skin, although this difference could possibly be explained by differential expression of chondroitin sulfates and dermatan sulfate and not HS [ 22 ]. Both the extracellular matrix in addition to the cell surface and the epithelial basement membrane seems to be the primary site of virus binding during genital tract infection in vivo [ 23 ] and a dynamic model for alpha-HPV entry has been suggested where binding of alpha HPV to cell surface HS results in conformational change in the capsid, followed by binding to a second receptor [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study comparing HS expression in skin and mucosa, more GAGs were found in vaginal tissue than in perianal skin, although this difference could possibly be explained by differential expression of chondroitin sulfates and dermatan sulfate and not HS [ 22 ]. Both the extracellular matrix in addition to the cell surface and the epithelial basement membrane seems to be the primary site of virus binding during genital tract infection in vivo [ 23 ] and a dynamic model for alpha-HPV entry has been suggested where binding of alpha HPV to cell surface HS results in conformational change in the capsid, followed by binding to a second receptor [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bezerra et al 25 found significant differences among GAGs in vaginal tissue. Total amounts of GAG, CS, DS, and HS in premenopausal women with prolapse stages I, II, and III were significantly higher than in postmenopausal patients with prolapse stages II and III.…”
Section: Discussionmentioning
confidence: 98%
“…Our study focused on GAGs reported in previous studies 19 . We identified a high amount of hyaluronic acid, which was the most prevalent GAG in all tissues studied (parametrium, vaginal apex and paraurethral tissue).…”
Section: Discussionmentioning
confidence: 99%